Sustainable solid waste management in leather and textile industry : leather & textile waste fibre-polymer composite and nanocomposite : overview and review - Sivakumar, Venkatasubramanian (Array, 2020)
Proper disposal methods and solid waste management are necessary for all the processing industries such as leather, textile and chemical industry. In this regard, the present paper reviews in detail about the leather and textile waste fibre-polymer composites and nanocomposites as a viable solid waste management strategy. In the paper, several published papers and patents available in this area are reviewed in detail. This approach adopts confinement of leather or textile waste fibres in a polymer matrix as a composite. Nanocomposites of leather waste fibre and polymer with nano-particle reinforcement have been reported to have enhanced physical and other properties. This would not only solve the problem of the disposal issue regarding leather solid wastes containing leather or textile waste fibres, but also provide versatile composite or nanocomposite materials as “Wealth from Waste Approach”. The unique feature of the present analysis and the review paper is that both leather and textile waste management have been covered in the present approach for the first time.